Looking inward: devotional reading and the private self in late medieval England - Bryan, Jennifer (The Middle ages series, 2008)
A very inward man -- Seeing a difference : mirrors and texts -- Private passions -- Profitable sights : the showings of Julian of Norwich -- Hoccleve's glasses